Oral health in patients with COVID-19: a literature review - Nina E. Novozhilova; Anna V. Pianzina; Victoria A. Korol (Russian Open Medical Journal)
This article reviews the most common oral health problems, which could be associated with coronavirus disease 2019 (COVID-19). Several reports were published, which described various oral manifestations of COVID, including dysgeusia, petechiae, candidiasis, traumatic ulcers, herpesvirus infection, geographic tongue, thrush like ulcers, among others. Alterations of smell and taste seem to be the most common manifestations of COVID in the orofacial area, which could be directly related to the effect of the virus. Other oral conditions seem to be secondary to the decrease of host defense, or else caused by the drugs and intensive care used in the treatment of COVID-19.